Reflective processes and competencies involved in teaching practice at university: a case study - Caetano da Costa; Lisete Diniz Ribas Casagrande; Julieta Ueta (Faculdade de Medicina de Botucatu (Unesp), 2010)
Founded on practical rationality, this qualitative case study aimed to explore the teaching practice at university, focusing on teacher's reflections and competencies. To this end, teaching practices were described, analyzed, and interpreted. These interactions with students on a course in the pharmacy program, brought about situations involving dilemmas and learning opportunities for problem-solving and decision-making skills. Throughout the study, students were encouraged to use knowledge-in-action, reflection-in-action, and reflection-on-action, and these processes were also experienced by the teacher. Analysis of the records from classroom observation and the interviews with students and the teacher showed the fundamental role of such reflective processes, which led to attainment of the intended objectives. In this sense, the teacher's reflective practice was essential for supporting the application of each curricular component of the course.